Immunohistochemical evaluation of myofibroblasts using alpha-smooth muscle actin in oral submucous fibrosis - Teena Philip; T Dinesh Kumar; K Rajkumar; K Raghavendhar Karthik; N Priyadharsini; A Ramesh Kumar (SRM Journal of Research in Dental Sciences, 2014)
Introduction: Oral submucous fibrosis (OSMF) is a chronic debilitating disease and a premalignant condition of the oral cavity characterized by generalized submucosal fibrosis with a multifactorial etiology. Myofibroblasts are a unique group of cells phenotypically intermediate between smooth muscle cells and fibroblast exhibiting contractile properties, expressing α-smooth muscle actin (α-SMA) and are considered primary producers of extracellular matrix after injury. Their accumulation has been established as a marker of progressive fibrosis in various organs. The aim of the present study is to evaluate and compare the myofibroblasts in various histological grades of OSMF. Materials and Method: Fifteen cases of OSMF, which were further categorized histologically into early (5 cases), moderately advanced (5 cases) and advanced (5 cases), were subjected to immunohistochemical evaluation using α-SMA antibody for detection of myofibroblasts. Fifteen benign mucosal proliferation specimens were also stained for comparison. Results: The number of myofibroblasts in OSMF was significantly increased when compared to that of benign mucosal proliferations (P < 0.05). Additionally, a statistically significant increase in the myofibroblasts population between early and advanced stages was observed (P < 0.05). Conclusions: The results of the present study showed that expression of myofibroblasts within the OSMF group showed a progressive increase from the early OSMF through moderate OSMF and the advanced OSMF group indicating that myofibroblasts could serve as effective prognostic marker for disease progression in oral submucous fibrosis.